Peran Sukuk Terhadap Pembangunan Infrastruktur - Robin; Diah Putri Febiana Sari; Kharis Fadhullah Hana (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2020)
Infrastructure development with Sukuk is currently developing rapidly. Sukuk are bonds based on Islamic principles. Sukuk have lower refund rates compared to interest-based bonds. This study aims to explain the role of Sukuk in infrastructure development in Indonesia. This research uses qualitative methods that are analyzed descriptively. With secondary data derived from the literature review in the form of the results of previous studies, documents from valid institutions or institutions, news, and other supporting sources. The results show that Sukuk is an important financial instrument applied in infrastructure development and has a positive contribution to infrastructure development. Since it was published until February 13, 2020, the accumulation of SBSN issuance results has reached Rp. 1,253.4 T. The results of the issuance of the Sukuk were used by the government to finance various infrastructure projects in Indonesia. So the Government can maximize the potential of Sukuk as an alternative to infrastructure financing and start reducing dependence on foreign debt in infrastructure financing